Military Operations in Response to Domestic Emergencies and Global Pandemics Implications for Civil-Military Relations - Heinecken, Lindy; Leuprecht, Christian; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book provides a comparative analysis of the deployment of the military in domestic operations, the use of the armed forces during the COVID-19 pandemic, and the impact of that deployment on civil-military relations in 26 countries worldwide. The book examines the legal and constitutional regulations under which the military can serve in domestic roles, and the extent of domestic deployment before the COVID-19 pandemic. It focuses on the roles in which the military served during the pandemic, the resources available, and the readiness and effectiveness of the military response. The volume addresses whether or not the pandemic response was securitized, the extent of civilian oversight and control, the accountability measures in place, and the impact of the COVID-19 deployment on the military$1 (Bs image. The volume captures the lessons learnt from the COVID-19 deployment and the implications for future force design, structure, and organizational transformation. Since almost all countries used their military in some capacity to respond to the COVID-19 pandemic, this volume offers an opportunity to compare use of the armed forces to provide domestic humanitarian assistance and disaster response.s
Acknowledgments -- Introduction: Overview of Military Operations in Response to Domestic Emergencies, Global Pandemics, and Civil-Military Relations -- United States -- United Kingdom -- Canada -- Australia -- New Zealand -- Larger Established Nato Members -- France -- Germany -- Italy -- Spain -- Smaller Established NATO Members: Portugal -- The Netherlands -- Belgium -- Denmark -- New NATO Members: Sweden -- Estonia -- Slovenia -- East and South Asia: Japan -- Korea -- Pakistan -- Philippines -- Latin America and Africa: Brazil -- Nigeria -- Sierra Leone -- South Africa -- Zimbabwe -- Namibia -- Conclusion -- Comparative Perspectives on Domestic Emergencies, The Pandemic Response and Civil-Military Relations.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Politics and war; Security systems; Political science; Military and Defence Studies; Security Science and Technology; Political Science